Pemilihan Karyawan Getah Pinus Terbaik Di PT.INHUTANI V GM SUMBAGUT Menggunakan Metode SAW: Pemilihan Karyawan Terbaik Menggunakan Metode SAW - Via Ningrum, Maratul Hasanah; Humairoh, Salsabila; Popi Amada, Elca; Lubis, Tiara (Fakultas Ilmu Komputer, 2024)
The best and qualified employees will make a company to be improved in its operations in the collection of pine resin to achieve the target. However, the constraints at PT INHUTANI V GM SUMBAGUT best employee award is still not optimal its implementation. Therefore, a system is needed that can assist the company in assessing the best employees optimally. Decision making to determine the best employee can be done by the company by assessing the performance that has been done by its employee at PT. INHUTANI V is influenced by several criteria, namely : Attendance, Teamwork, Colecction of the most pine sap, Responsibility, Sales of the most sap to the factory. This decision support system uses the Simple Additive Weighting (SAW) method where the decision-making process can be calculated based on the calculation of the weight of each criterion, so as to select the best employees in the company quickly.